Evidence of the effectiveness of caries risk management models (Revista Contexto & Saúde, 2026)
The search for a more comprehensive approach to oral health has led to the analysis of care models that integrate biophysical, psychological, and social dimensions, recognizing the complex interaction between these factors. Objective: To analyze the evidence of the effectiveness of caries risk management models for the adult population. Methods: This is a systematic review based on the PRISMA Preferred Reporting Items for Systematic Reviews. The search was conducted in the PubMed, SciELO; Scopus, and Web of Science databases in November 2024. Results: A total of 1,695 articles were identified, 1,633 of which were excluded in the screening process; 13 articles were included in this review. The studies applied software for caries risk management to 8,641 participants. The most widely used software in the adult population was Cariogram. A direct association was found between Cariogram risk categories and caries prevalence, experience, and severity. Risk factors such as previous history of the disease, salivary flow rate, mutans streptococcus levels, and dietary and oral hygiene habits have been found to be strong predictors of future caries incidence. Genetic factors, specific medical conditions, unique microbial characteristics, and even individual response to treatments can significantly influence caries risk. Conclusion: Caries risk management is a promising approach for the prevention and control of this disease. The use of software and applications can facilitate risk assessment and the creation of personalized treatment plans.
Keywords: Dental caries; Risk management; Disease prevention; Oral health